POLA KONSUMSI JAJANAN DAN STATUS GIZI ANAK DI SDN 5 KAWAN BANGLI - Arta Suryantini, Sang Ayu Made; Suiraoka, I Putu; Sri Sugiani, Pande Putu (Jurnal GIZIDO, 2024)
This research aims to determine the consumption patterns of snacks and the nutritional status of school children at Kawan Bangli Elementary School. This research is an observational type with a cross-sectional design. The population is all female students at SD Negeri 5 Bangli. A sample of 40 subjects was selected randomly and carried out in April 2024. Data was collected using a questionnaire, and SQ-FFQ Form and nutritional status data was taken by measuring body height and weight. The results of this study determined that the majority of the sample, namely 27.5% of people were undernourished, 42.5% were well nourished, 10.0% were overnourished, and 20.0% were obese. The pattern of snack consumption is that 10 samples (25%) consume main meals, 20 samples (50%) consume snacks, 5 samples (12.5%) consume drinks and, 5 samples (12.5%) consume snacks. fruit. The type most consumed by the sample is snacks, the number of samples consumed is 25 samples (62.5%) the amount of snack consumption is not as recommended > 300 kcal/day, as many as 15 samples (37.5%) the amount of snack consumption is as recommended < 300 kcal / day, the consumption frequency of 14 samples (35%) had a frequency of consuming snacks rarely < 7x a day, 26 samples (65%) had a frequency of snacking frequently > 7x a day.